Clinical Practice Guidelines for Pancreatic Cancer 2022 from the Japan Pancreas Society: a synopsis - Takuji Okusaka; Satoaki Nakamura; Masahiro Yoshida; Masayuki Kitano; Yoshinori Ito; Nobumasa Mizuno; Keiji Hanada; Masato Ozaka; Chigusa Morizane; Yoshifumi Takeyama; Yasunari Sakamoto; Dai Inoue; et al. (2023)
Clinical Practice Guidelines for Pancreatic Cancer was first published in 2006 by the Japan Pancreas Society, and revised in 2009, 2013, 2016, and 2019. In July 2022, Clinical Practice Guidelines for Pancreatic Cancer was newly revised in Japanese.For this revision, we developed an entirely new guideline according to the Minds Manual for Guideline Development 2020, which includes the concepts of GRADE-Grading Recommendations Assessment, Development, and Evaluation, to enable a better understanding of the current guidelines. Patients and the public were actively involved in both the development and implementation of the guideline.The guideline includes algorithms for diagnosis, treatment, chemotherapy, and precision medicine of pancreatic cancer, and addresses 7 subjects: diagnosis, surgical therapy, adjuvant therapy, radiation therapy, chemotherapy, stent therapy, and supportive & palliative medical care. It includes 73 clinical questions and 112 statements. The statements correspond to the clinical questions, evidence levels, recommendation strengths, and agreement rates.This guideline represents the most standard clinical and practical management guideline available until date in Japan. This is the English synopsis of the Clinical Practice Guidelines for Pancreatic Cancer 2022 in Japanese, and is an attempt to disseminate the Japanese guideline worldwide to introduce the Japanese approach to the clinical management of pancreatic cancer.